A Délvidék története Glad-országtól 1323-ig = History of "Délvidék" of (South-Hungary) from Glad-country to 1308 - Gulyás, László (Közép-Európai Közlemények, 2018)
The author of this essay was dealing with the history of South Hungary in several book1 and article.2 This essay survays the history of this region from Hungarian settlement3 (896) to 1323. The first stucture of this region was the so-called Glad-country, although the existance of it is disputed by historians. In the first part of our essay we survay the features of this state. The next state was Ajtony’s state at the end of 9th, and at the beginning of 10th centuries. This state – according to our opinion – was failed in 1027-1028. The main reasons of this we examined int he second part of our essay. After the end of Ajtony’s state, St. Stephan started to develop the county system. In the third part of our essay we are dealing with the history of counties. In the last part of our essay we survay that period (1307-1323), when the biggest township of the region functioned as capital of Hungary.